Food- evoked emotions: comforting hints and psychophysics - Pinto, Vinícius Rodrigues Arruda (2022)
Emotions evoked by food provide valuable information in new product development. A series of instruments have recently been proposed to capture emotional responses elicited by food to assess the total consumer experience. The use of emojis as an assessment tool is a potential current example. The literature has shown that the emotional profile provides additional information beyond the domain of taste, although it is still a challenge to use it to differentiate hedonically similar or utilitarian stimuli. Ideally, emotional and sensory profiles have been used together for better decision making, because the food contexts evaluated reveal perceptions at a multifactorial level. For example, new insect-based, plant-based, or meat-based products are strongly associated with sociocultural aspects, which makes their emotional profiles conditioned to hedonism. On the other hand, in scenarios determined by mood, as in the case of consumers suffering from some psychopathology, the emotional profile will be crucial and more determinant than hedonism. The objective of this research was to evaluate the emotional profiles of new foods in relation to the healthiness aspect, followed by the proposition of new sensory thresholds of emotion. To meet the objectives, the work was divided into four articles. In the first article, a study was carried out to survey perceptions around the healthiness of foods. The content analysis identified five dimensions: ‘misconception, knowledge or cognition’, ‘pleasure’, ‘importance of health’, ‘purity’, and ‘ethical or environmentally friendly issues’. Overall, the desire for more palatable “healthy” foods may explain increasing attention to future foods that provide positive feelings (e.g., green comfort foods). In the second article, a broad view of how contemporary foods changed the concept of comfort foods was provided. Semi- structured interviews with 20 Brazilian participants showed that cultural predilections, health concerns, self-awareness, past experiences, familiarity, satiety, and taste can explain why comfort food preferences range from healthy to unhealthy foods, and from traditional foods to contemporaries. The psychological manifestation of comfort was more closely related to a sense of morality associated with healthier foods. In the third article, the acceptance, purchase intention, and emotional responses of consumers to mixed dairy drinks, with and without the addition of kefir, were evaluated, considering blind and informed conditions. Overall, expressions of positive emotion increased when participants were exposed to stimuli related to the health benefits of kefir (15%, 30%, and 50% w/v). The information provided from kefir modified valence and arousal in subjects, and emojis proved to be viable to predict acceptability and purchase intention, although there are still controversies around arousal. Finally, the fourth article aimed to elucidate three new thresholds: the valence thresholds, represented by the compromised pleasure threshold (CPT) and unpleasure threshold (UT), and the arousal threshold (LA). The valence and arousal ratings were obtained using the Affective Slider (AS) rating scale, and CPT, UT, and AT were determined for images of Brazilian moldy carrot cake. The moldy carrot cake had negative valence in the region of low arousal. The methodology proved to be adequate to propose emotion thresholds, which highlights its potential to generate a deeper understanding of the psychophysiological reactions evoked from comforting stimuli. In this way, opportunities for psychoeducational interventions and improvements in decision- making may be more frequent in the studies, considering the positive association between experiences of comfort and healthiness to be more common. Keywords: Comforting. Emoji. Emotion. Emotion thresholds. Healthiness.